Spray and flame characteristics of wall-impinging diesel fuel spray at different wall temperatures and ambient pressures in a constant volume combustion vessel. (1st January 2019) - Chen, Beiling; Feng, Lei; Wang, Yu; Ma, Tianyu; Liu, Haifeng; Geng, Chao; Yao, Mingfa
Highlights: Liquid phase of fuel will not impinge on the wall as ambient pressure increases. Ambient pressure has a significant influence on the auto-ignition position. Wall temp. has more obvious influence on flame structures at lower ambient pressure. Wall temp. has a strong correlation with flame luminosity, ignition delay & soot. Abstract: The qualitative mixture concentration distributions and the flame characteristics of wall-impinging diesel fuel spray at different wall temperatures and ambient pressures were investigated in a high-temperature high-pressure constant volume combustion vessel. The techniques of laser induced exciplex fluorescence (LIEF) and flame natural luminosity imaging have been used to visualize the liquid and vapor phases of the spray and the flame development process respectively. Results reveal that, as the wall temperature increases, the vapor-rich field extends to the region close to the wall and the area of high vapor fluorescence intensity increases. However, the wall temperature only has a little influence on the liquid phase of the spray. The flame luminosity intensity increases and the ignition delay decreases as the wall temperature increases. Cases at higher wall temperature show more soot emissions, higher soot formation and oxidation rate. In the condition of P a = 4 MPa, the fuel has evaporated completely before impinging on the wall. The flame area and height at different wall temperatures are nearly the same. The ignition position is observed near the impingement point. However, in the condition of P a = 2 MPa, there are some liquid phase of the fuel impinging on the wall. The flame area and height increase as the wall temperature increases. The ignition position is always observed in the wall jet region. The distance between ignition position and the axis of the spray decreases as the wall temperature increases.